2015
DOI: 10.1002/2015jd023382
|View full text |Cite
|
Sign up to set email alerts
|

Light‐absorbing properties of ambient black carbon and brown carbon from fossil fuel and biomass burning sources

Abstract: The optical properties of ambient black carbon-containing particles and the composition of their associated coatings were investigated at a downtown site in Toronto, Canada, for 2 weeks in June 2013. The objective was to assess the relationship between black carbon (BC) coating composition/thickness and absorption. The site was influenced by emissions from local vehicular traffic, wildfires in Quebec, and transboundary fossil fuel combustion emissions in the United States. Mass concentrations of BC and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
102
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 75 publications
9
102
2
Order By: Relevance
“…It is a group of species with specific physical properties but detailed chemical components that are difficult to characterize. BrC can be produced not only from primary emissions relating to biomass burning (BB) and fuel combustion, but also from secondary organic aerosol (SOA) formation through the oxidation of volatile organic compounds (VOCs) (Andreae and Gelencsér, 2006;Saleh et al, 2014;Chen and Bond, 2010;Lack et al, 2012;Laskin et al, 2015;Healy et al, 2015). Some studies reported that vehicle and ship emissions may also be sources of BrC (Stone et al, 2009;Cavalli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a group of species with specific physical properties but detailed chemical components that are difficult to characterize. BrC can be produced not only from primary emissions relating to biomass burning (BB) and fuel combustion, but also from secondary organic aerosol (SOA) formation through the oxidation of volatile organic compounds (VOCs) (Andreae and Gelencsér, 2006;Saleh et al, 2014;Chen and Bond, 2010;Lack et al, 2012;Laskin et al, 2015;Healy et al, 2015). Some studies reported that vehicle and ship emissions may also be sources of BrC (Stone et al, 2009;Cavalli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the difference of wavelength dependence for BC and BrC, previous studies segregated light absorption of BrC from multi-wavelength optical measurements (Lack and Langridge, 2013;Mohr et al, 2013;Shen et al, 2017), which is called the AAE method. Earlier, the similar concept was used to segregate carbonaceous aerosol fractions from different emission sources based on their difference in AAE value (e.g., wood burning and traffic emission) (Sandradewi et al, 2008;Healy et al, 2012). Usually, the AAE of BC (AAE BC ) was set to be 1.0 based on the properties of bulk BC by many previous studies, assuming the unity of AAE BC between any two wavelengths within the UV to the near-infrared (IR) range (Shen et al, 2017;Olson et al, 2015;Lack and Langridge, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…If the temperature is too low, the coating cannot be fully removed, and charring can occur if the TD temperature is too high, leading to biased results. For example, a soot particle aerosol mass spectrometer (SP-AMS) study in Toronto found that the efficiency of BC coating removal by TD decreased substantially for wildfire-influenced samples (Healy et al, 2015). Another issue is particle loss due to TD, which can be ∼ 20 % and needs to be taken into account (Ueda et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, source apportionment using high time resolution OA mass spectra measured by an aerosol mass spectrometer (AMS) or an aerosol chemical speciation monitor (ACSM) has been a useful approach to reduce the dimensionality of complex organic 15 fractions into more easily interpretable OA factors (e.g. Ulbrich et al, 2009;He et al, 2010;Ng et al, 2011;Crippa et al, 2013;Bougiatioti et al, 2014;Lee et al, 2015). Three primary factors: hydrocarbon-like organic aerosol (HOA), cooking organic aerosol (COA), and biomass burning organic aerosol (BBOA), are commonly identified in many locations.…”
mentioning
confidence: 99%